Women in the Ancient Near East - Stol, Marten (De Gruyter, 2016)
Women in the Ancient Near East offers a lucid account of the daily life of women in Mesopotamia from the third millennium BCE until the beginning of the Hellenistic period. The book systematically presents the lives of women emerging from the available cuneiform material and discusses modern scholarly opinion. Stol's book is the first full-scale treatment of the history of women in the Ancient Near East.